BERBAGI KECERIAAN BERSAMA YAYASAN KASIH ANAK KANKER INDONESIA (YKAKI) CABANG MAKASSAR - Anita Achmad Payu; Mariah Mariah (Nobel Community Services Journal, 2022)
Cancer is one of the non-communicable diseases which is a public health problem, both in the world and in Indonesia. This disease does not only attack the adult age group, but also children under the age of 18 years. Cancer can even spread since the child is still in the womb. Unlike cancers in adults, most childhood cancers have no known cause. Many studies have attempted to identify the causes of childhood cancer, but very few childhood cancers are caused by environmental or lifestyle factors. Seeing the number of children with cancer is not small, serious treatment is needed to control the disease. In Indonesia, many control efforts have been carried out by the Ministry of Health of the Republic of Indonesia and other parties outside the government, one of which is Yayasan Kasih Kanker Anak Indonesia (YKAKI).This service is carried out to provide motivation for children with cancer, especially those at the Makassar Branch of the Indonesian Cancer Child Care Foundation (YKAKI) where in this activity collaboration between lecturers and students from Himpunan Mahasiswa Jurusan Akuntansi (HMJA). It is hoped that this activity can provide motivation and share with children with cancer so that they remain enthusiastic in living life full of joy.